2007
DOI: 10.1143/jpsj.76.054501
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Collisional Drift and Flute Wave Instabilities in Bounded Linear ECR Plasma

Abstract: This paper reports the experimental and theoretical investigation on the coexistence of the collisional drift and flute wave instabilities in the bounded linear electron cyclotron resonance (ECR) plasma. The drift wave instability is excited by the steep density gradient and imposed axial boundary conditions in the device. The flute instability is excited by the bad curvature of the magnetic field. Emphasis is made on the effect of the ion-neutral (i-n) particle collisions. It is observed that the drift wave i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 28 publications
(30 reference statements)
1
23
0
Order By: Relevance
“…4. 9 Instead, upon further investigation as will be shown later, we find that this pressure region (p Շ 1.5 mTorr) is dominated by drift waves.…”
Section: (A)-4(c)mentioning
confidence: 58%
See 1 more Smart Citation
“…4. 9 Instead, upon further investigation as will be shown later, we find that this pressure region (p Շ 1.5 mTorr) is dominated by drift waves.…”
Section: (A)-4(c)mentioning
confidence: 58%
“…The coexistence between the drift and flute wave instabilities in a linear ECR plasma has been studied with an axially imposed boundary. 9 Shoyama et al 10 found intense coherent fluctuations in the ion saturation current when a negative bias was applied to a hollow cathode target in an ECR plasma. Later, lowfrequency fluctuations in an ECR plasma source have been investigated with respect to stabilization by localized, radial electric fields by means of a biased, segmented end plate.…”
Section: Introductionmentioning
confidence: 99%
“…Here, z is measured from the coaxial waveguide converter. The θ coordinate is defined such that the vertical (downward) direction from the center of the device has a θ of 270 degrees [13]. The cross phases in both azimuthal and axial directions are regarded as near zero within the present error bars, and show the azimuthal and axial symmetric structures of (m, n) = (0, 0), similar to a zonal flow structure.…”
mentioning
confidence: 99%
“…However, the interaction of externally induced time varying E × B shear flow with the drift mode has not been reported. In this letter, we present experimental observations of the impact of an oscillation driven by a small modulation of ECR power, which has the zonal flow structure (called a zonal flow type author's e-mail: kamataki@riam.kyushu-u.ac.jp oscillation in this letter), on the drift wave.Experiments are performed in the region of lower ionneutral collision frequency ν in /Ω i ∼ 0.4 (filling gas pressure p (Ar) = 0.6 ×10 −3 Torr), where the drift mode is strongly excited in a linear cylindrical electron cyclotron resonance (ECR) plasma [13]. Here, ν in and Ω i indicate the ion-neutral collision frequency and the ion cyclotron frequency, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation